HORMONAL INTERACTION AND FACIAL AGING: A LITERATURE REVIEW (REMUNOM, 2026)
Understanding the hormonal mechanisms that drive age-related changes in facial tissues is key to appreciating how these factors shape the aging process. This study aimed to review the scientific literature to assess the influence of endocrine hormones on age-related morphological changes, highlighting how these biological mediators impact the visible features of the face over time. Evidence suggests that hormonal balance plays a central role in maintaining the structure and function of the skin, muscles, bones, and facial adipose tissue. The progressive decline of sex hormones—such as estrogen in women and testosterone in men—is linked to reduced skin elasticity, decreased bone density, and loss of muscle mass. Additionally, elevated cortisol levels accelerate physical and cognitive decline, while reductions in growth-related hormones, including GH and IGF-1, exacerbate muscle wasting and promote an increase in adipose tissue. Unraveling these pathways is essential for guiding interventions aimed at fostering healthier aging and preserving quality of life in older adults.